Does Seeking Audit Evidence Impede the Willingness to Impose Audit Adjustments? - Kachelmeier, Steven J.; Rimkus, Dan (The Accounting Review, 2022)
ABSTRACT In two incentivized auditing experiments, participants who choose to acquire evidence adjust for the risk revealed by that evidence to a lesser extent than those who obtain the same evidence without investigative action, controlling for the diagnostic value of evidence. This finding follows from mental accounting and information choice theories that, in combination, predict that choosing to undertake effortful investigation can magnify aversion to costly adjustments. In our first experiment, effort choice reduces adjustments only when the same participants make both decisions, not when different participants make these decisions in noninteractive pairs. We observe consistent findings in a second experiment that pairs all participants and allows interaction, with effort choice reducing adjustments only when participants responsible for evidence perceive high involvement in the adjustment decisions made by their paired counterparts. A potential implication of our study is that emerging audit technologies that facilitate evidence collection could also enhance auditor independence.